Legalization of Water Quality Standards as a Guarantee of Protection of the Right to Sustainable Life - Putu Samawati; Suci Flambonita; Nashriana Nashriana; Seguito Monteiro (Nurani, 2025)
Water is essential for all forms of life, and its importance is also emphasized in Islamic teachings. The quality of water that is not guaranteed can affect health or even the validity of worship. Base on the problem, the existence of water becomes important, especially in efforts to ensure the hygiene of water quality standards in order to provide security for its users. The existence of water requires guaranteed protection from supply to distribution. In fact, it is not governed by strict regulations that ensure legal certainty. This study aims to describe the level of urgency of legalizing water and sanitation quality standards in the form of higher and legally binding regulations. Empirical legal methods by taking primary and secondary data sources in conducting problem analysis. Observations and interviews were conducted to obtain primary data, while secondary data was obtained from legislative and conceptual approach are used to strengthen arguments in ensuring that the concepts offered remain in the correct legal corridor. The findings show the inconsistency of the government in recognizing the existence of water that is important for life but the implementation of systematic quality standard supervision, even the application of sanctions for violators cannot be carried out because the legal instrument is only limited to the regulations of the Minister of Health. The need to establish regulations in the form of Government Regulations on water quality standards and sanitation is a crucial consideration for safeguarding public health and well-being.